1998
DOI: 10.1136/thx.53.4.254
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae and asthma

Abstract: Background-This study was designed to test the association of Chlamydia pneumoniae infection with asthma in a multiracial population, after adjustments for several potential confounding variables. Methods-Antibodies to C pneumoniae were measured by microimmunofluorescence in 123 patients with acute asthma, 1518 control subjects admitted to the same hospital with various non-cardiovascular, non-pulmonary disorders, and 46 patients with severe chronic asthma, including some with "brittle" asthma. Acute infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 43 publications
3
64
0
5
Order By: Relevance
“…As proposed by EKMAN et al [18] a MIF IgA titre $512 was also considered as evidence of acute infection. There are no firm criteria for serological evidence of previous or persistent infection, thus an IgG titre $64 and <512, or an IgA titre $16 and <512 were considered indicative of previous or persistent infection [19].…”
Section: Chlamydia Pneumoniae Serologymentioning
confidence: 99%
“…As proposed by EKMAN et al [18] a MIF IgA titre $512 was also considered as evidence of acute infection. There are no firm criteria for serological evidence of previous or persistent infection, thus an IgG titre $64 and <512, or an IgA titre $16 and <512 were considered indicative of previous or persistent infection [19].…”
Section: Chlamydia Pneumoniae Serologymentioning
confidence: 99%
“…Recent studies have suggested that this organism may have a role in the pathogenesis of newly diagnosed and chronic stable asthma in both adults and children [9][10][11][12][13]. However, these studies have been based on serological tests, which cannot reliably differentiate between past and present infection or acute and chronic infection and which may be cross-reactive with other Chlamydia species.…”
mentioning
confidence: 99%
“…Infection with Chlamydophila pneumoniae, an obligately intracellular pathogen, has been suggested to be associated with severe non-atopic asthma (Cook et al, 1998), corticosteroid -dependent or -resistant asthma (Black et al, 2000;Hahn et al, 1998;von Hertzen et al, 2002), and asthma with persistent airflow limitation (Pasternack et al, 2005;ten Brinke, 2008). C. pneumoniae has an innate propensity to persist, and can cause chronic or latent infections in various structural and immune cells.…”
Section: Introductionmentioning
confidence: 99%